Prevalence of dental fluorosis among primary school children in Thamar- Yemen. - Faraed D Salman (University of Mosul, College of Dentistry, 2007)
Aims: To determine the prevalence and severity of dental fluorosis in relation to age and sex for primary school children, aged 6 - 12 years old in Thamar -Yemen. Material and methods: The study included 600 primary school children aged 6, 9 and 12 years old randomly selected (300 males, 300 females) in Thamar - Yemen, who had lived since birth in moderate natural fluoride level (1.8 - 2.2 ppm) by the use of Dean index to assess dental fluorosis. Results: Showed that the prevalence of dental fluorosis was 19.83 % and 5.23 % within students and teeth respectively, ranging from very mild to moderate form of dental fluorosis with no significant sex difference for individuals at p ≤0.05 as total and significant difference between males and females for teeth as total at p ≤ 0.001, the percentage of severity had been found to be increasing with age. The community fluorosis index for Thamar Province was 0.4 %, which was regarded low. Conclusion: The prevalence of dental fluorosis had been increased with increasing age with no sex difference